Deconstructing the causes of July sea level variability in the East Sea from 1994 to 2021 - Han, MyeongHee; Chang, Yeon S.; Yoo, Jeseon (Frontiers in Marine Science, 2023)
In 2021 the East Sea experienced its highest July sea level (65.09 cm), as well as the highest July sea surface and atmospheric temperatures, in the 29 years between 1993 and 2021. We present several methodologies to identify the more important causes of sea level change (SLC) in a semi-enclosed sea and explore the critical fluctuation of ocean mass transport divergence during a period of rapid sea level rise. Based on satellite altimeter data in the East Sea, the SLC, as reflected in the absolute dynamic topography (ADT), which is the ADT difference between the last and first days of a month, was 7.18 cm in July 2021. This may reflect a combination of oceanic and atmospheric factors: ocean heat transport divergence among the Korea, Tsugaru, and Soya Straits was found to contribute 2.32 cm of SLC, atmospheric heat flux at the sea surface contributed 2.87 cm of SLC, and mass divergence (including errors) accounted for 1.98 cm of SLC. The monthly mean sea level (ADT) variation in the East Sea should be examined in terms of the oceanic and atmospheric fluxes, and the SLC sources can additionally be divided into heat and others (mass + errors). The proportional contribution of heat to SLC from 1994 to 2021 was 97.4%. Although the contributions of mass and errors were small, there were substantial temporal fluctuations, as their standard deviation reached up to 96.7% of that of SLC in ADT. In the near future, a more precise analysis of the contributions of mass and errors to SLC is required.